What about my daughter's future? Parental concerns when considering female genital restoration surgery in girls with congenital adrenal hyperplasia. Issue 5 (October 2018) - Szymanski, K.M.; Whittam, B.; Kaefer, M.; Frady, H.; Cain, M.P.; Rink, R.C.
Summary: Purpose: The parental decision-making process regarding female genital restoration surgery (FGRS) for girls with congenital adrenal hyperplasia (CAH) is controversial and poorly understood. The aim of the study aim was to evaluate parental concerns related to their child's future and parental plans about disclosure prior to FGRS. Materials and methods: The authors performed an online survey of consecutive parents presenting at a tertiary referral center for consultation regarding FGRS for their daughter with CAH before 3 years of age (2016–2018). Twenty issues initially identified by three families and six clinicians were rated on a 6-point Likert scale of importance ('not at all' to 'extremely'). Results: Sixteen consecutive families participated (Prader 3/4/5: 43.8%/43.8%/12.5%). Fourteen girls (87.5%) subsequently underwent FGRS at a median age of 8 months. Most issues (19/20, 95.0%) were ranked 'quite a bit' to 'extremely' important (Table ). Top issues were not surgical: Normal physical/mental development, adrenal crisis and side-effects of medications. Surgery-related and self-image concerns followed in importance. Least prioritized issues were multiple genital exams ('quite a bit' important) and the child not being involved in the decision to proceed with FGRS ('somewhat' important). On average, no issues were considered 'not at all' or 'a little' important. Disclosure of FGRS to their daughter was the 15th prioritized issues. Almost all families (93.8%, 1 unsure) planned to disclose the surgery to their daughter, although many were unsure when and how to do it (33.3% and 37.5%, respectively). Comment: Initial efforts to understand the complex process of parental decision-making regarding FGRS in the context of CAH, a complex, multifactorial disease, are presented. Parents of infant girls with CAH simultaneously weigh multiple life-threatening concerns with a decision about FGRS. While issues of genital ambiguity and surgery are important, they are not overriding concerns for parents of girls with CAH. Parents report significant uncertainty about appropriate timing and approach to disclosing FGRS to their daughters. Unfortunately, best practice guidelines for this process are lacking. The findings are not based on actual history of disclosure but on parents' anticipated behavior. Further data are need from parents, children, and women with CAH about successful disclosure. Being a single-center series, these data may not correspond to the wider CAH community. Conclusions: Parental decision-making regarding FGRS is multifactorial. Even when considering FGRS, parents' largest concerns remain focused on the life-threatening and developmental effects of CAH and side-effects of its medical treatment. The disclosure process deserves further attention. Table Parent-reported importance of issues prior to female genital restoration surgery (no issue had a mean important score below 'somewhat' important, n  = 16). Rank Category Issue Importance score Importance category 1 Developmental Normal physical and mental development 92.5 Extremely (90.0–100.0) 2 Medical My child having an adrenal crisis 88.8 Very much (70.0–89.9) 3 Medical Side-effects from medications 88.8 4 Surgery/genital My child's future ability to have children 85.0 5 Surgery/genital My child's future ability for sexual intercourse 80.0 6 Developmental My child having problems with her self-image 80.0 7 Surgery/genital My child having a complication after surgery 78.8 8 Developmental Not letting CAH define her life 77.5 9 Surgery/genital General appearance of my child's genitalia 76.7 10 Surgery/genital My child needing possible future surgery 76.7 11 Surgery/genital Decreased sensation of my child's clitoris 72.5 12 Developmental My child's future gender identity 67.5 Quite a bit (50.0–69.9) 13 Medical Privacy about my child's medical history 65.0 14 Surgery/genital Size of my child's clitoris 65.0 15 Surgery/genital Disclosing the surgery to my child 63.8 16 Family stress Stress on our family 61.3 17 Developmental How other people will view my child 58.8 18 Developmental My child finding love and acceptance in the future 57.5 19 Surgery/genital My child having multiple genital exams by doctors in the future 50.0 20 Surgery/genital My child not having had a voice in choosing surgery 28.8 Somewhat (30.0–49.9) n/a n/a n/a n/a A little (10.0–29.9) n/a n/a n/a n/a Not at all (0.0–9.9) CAH, congenital adrenal hyperplasia.